Increasing moral values through sports: systematic literature review - Asep Ramdan Afriyuandi; Teguh Satria; Cece Rakhmat; Carsiwan Carsiwan (Universitas Suryakancana, 2025)
This research aims to analyze the contribution of sport in improving individual moral values through a systematic literature review approach. This study evaluates various relevant literature to identify the relationship between participation in sports activities and the development of moral values, such as honesty, responsibility, cooperation and respect. Through systematic selection and analysis of data from journals, books and research reports, it was found that sport can be an effective medium in moral formation, especially through social interaction, healthy competition and application of game rules. Factors such as the role of the coach, the sporting environment and the type of sport undertaken also influence the extent to which moral values can be developed. This finding also shows that the integration of moral values in sports does not happen automatically but requires a structured approach and awareness from all parties involved. Therefore, it is important to design training programs that do not only focus on the physical aspect but also emphasize the learning of ethical values explicitly. The results of this research provide insight for educational practitioners, sports coaches, and policy makers to integrate moral values into sports programs as a character building strategy.